MSC-EXs inhibits uranium nephrotoxicity by competitively binding key proteins and inhibiting ROS production - Xinrui Yang; Jing Liu; Yaru Yin; Luxun Yang; Mingquan Gao; Zifei Wu; Binghui Lu; Shenglin Luo; Weidong Wang; Rong Li (Ecotoxicology and Environmental Safety)
Uranium poisoning, particularly from exposure to Depleted Uranium (DU), occurs when uranyl ions enter the bloodstream and bind primarily to transferrin, osteopontin, and albumin before entering cells via corresponding receptors on renal tubular membranes, leading to cellular damage. Uranium poisoning remains a significant clinical challenge, with no ideal treatment currently available. In this study, we investigate the therapeutic potential of human umbilical cord-derived mesenchymal stem cell exosomes (MSC-EXs) in mice exposed to DU. Our results showed that MSC-EXs could ameliorate renal damage and enhance kidney and bone marrow morphology but also effectively promote uranium excretion while reducing internal retention. Notably, the protective effects of MSC-EXs exceed those of MSCs and are comparable to those of sodium bicarbonate, as confirmed by various analytical techniques. Proteomic studies have shown that MSC-EXs reduce uranyl ion deposition in renal tubule cells through competitive binding with transferrin, osteopontin, and albumin. They also enhance oxidative stress resistance via modulation of glutathione metabolism, Cysteine and Methionine metabolism signaling pathways. This regulation leads to a reduction in mitochondrial ROS production, alleviates lipid peroxidation, and consequently decreases cellular apoptosis and ferroptosis. This study identifies MSC-EXs as a novel therapeutic strategy against depleted uranium poisoning, presenting potential advancements in treatment methodologies.